2019
DOI: 10.1016/j.pacs.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Current and future trends in photoacoustic breast imaging

Abstract: Non-invasive detection of breast cancer has been regarded as the holy grail of applications for photoacoustic (optoacoustic) imaging right from the early days of re-discovery of the method. Two-and-a-half decades later we report on the state-of-the-art in photoacoustic breast imaging technology and clinical studies. Even within the single application of breast imaging, we find imagers with various measurement geometries, ultrasound detection characteristics, illumination schemes, and image reconstruction strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
148
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(148 citation statements)
references
References 122 publications
0
148
0
Order By: Relevance
“…In addition, several review papers for OA breast imaging have compared the visualization approaches of various imaging devices, along with the corresponding tumors features that were clinically detected. [1][2][3][4][5]12,19,20,43 5. 71 describes implementation and the associated challenges with these approaches in detail.…”
Section: Other Oa Visualization Approaches For Clinical Breast Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, several review papers for OA breast imaging have compared the visualization approaches of various imaging devices, along with the corresponding tumors features that were clinically detected. [1][2][3][4][5]12,19,20,43 5. 71 describes implementation and the associated challenges with these approaches in detail.…”
Section: Other Oa Visualization Approaches For Clinical Breast Imagingmentioning
confidence: 99%
“…[1][2][3][4][5][6] For breast cancer diagnosis, one promising technique is OA imaging combined with ultrasound (OA/US). [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Combining OA with ultrasound is advantageous because each modality provides information that is complementary to the other. Structural and functional information pertaining to total hemoglobin concentration (c tHb ) and blood oxygen saturation (s O 2 ) can be visualized with OA, while morphological and anatomical information can be obtained with ultrasound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steinberg et al [34], presented various clinical studies performed using PA imaging. In some recent review articles [52,53], the state of the art PA imaging systems, as well as the clinical studies for breast cancer diagnosis using PA imaging, were reported.…”
Section: Introductionmentioning
confidence: 99%
“…This gives the readers a complete picture of the development of PA imaging systems for breast cancer management. The recent review articles [48,52] only focused on clinical PA imaging studies which did not include phantom studies, animal studies using endogenous and exogenous contrast agents (dyes and nanoparticles) for breast cancer detection as well as SLN detection, ex vivo studies with human breast tissue samples.…”
Section: Introductionmentioning
confidence: 99%